2009
DOI: 10.1111/j.1755-148x.2008.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of melanoma brain metastasis by targeting melanotransferrin at the cell surface

Abstract: Brain metastases are a common feature of malignant melanoma and are associated with poor prognosis. Melanotransferrin (MTf), one of several antigens associated with the surface of melanoma cells, has been demonstrated to promote cell invasion. In this study, we investigated the role of membrane-bound MTf in several of the steps leading to the development of melanoma brain metastasis. Our results indicated that MTf-positive cells were detected in the brains of nude mice injected intravenously with human melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
(73 reference statements)
1
52
0
Order By: Relevance
“…Feng and others have hypothesized that matrix metalloproteinases secreted by leukemic cells may facilitate the breakdown of the blood-brain barrier (BBB), which may lead to seeding of the CSF during transient bacteremia (20). Additionally, melanoma is known to disrupt the BBB, and in our patient, disruption of the BBB by metastatic melanoma might have facilitated P. acnes to enter the CSF; however, it is unclear why P. acnes and not another organism might cause disease in this setting (21,22). While many scenarios could be hypothesized, one possible explanation is that the patient had a transient P. acnes bacteremia after his lower-extremity biopsy 8 weeks prior to admission that resulted in seeding of the CSF.…”
Section: Case Reportmentioning
confidence: 71%
“…Feng and others have hypothesized that matrix metalloproteinases secreted by leukemic cells may facilitate the breakdown of the blood-brain barrier (BBB), which may lead to seeding of the CSF during transient bacteremia (20). Additionally, melanoma is known to disrupt the BBB, and in our patient, disruption of the BBB by metastatic melanoma might have facilitated P. acnes to enter the CSF; however, it is unclear why P. acnes and not another organism might cause disease in this setting (21,22). While many scenarios could be hypothesized, one possible explanation is that the patient had a transient P. acnes bacteremia after his lower-extremity biopsy 8 weeks prior to admission that resulted in seeding of the CSF.…”
Section: Case Reportmentioning
confidence: 71%
“…First, large hydrophilic molecules, including many chemotherapeutic, are excluded from the CNS unless they can be actively transported by receptor-mediated transcytosis (58). Moreover, endothelial prognostic indicator for the development of brain metastases among patients with malignant melanoma (64). Another study reported that signal transducer and activator of transcription 3 (STAT3) activity was markedly elevated in human brain metastatic melanoma cells compared with cutaneous melanoma cells, suggesting close association between STAT3 expression and melanoma cell migration to the brain (19).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have demonstrated that different types of melanoma cells reduced transendothelial electrical resistance of the endothelial cell monolayer, indicating that specific tumor cells can modulate junctional integrity (22). It was also reported that the ability of melanoma cells to pass through the BBB corresponds closely with melanotransferrin (MTf) expression (22,64). MTf is one of several antigens associated with the surface of melanoma cells.…”
Section: Extravasationmentioning
confidence: 99%
“…[42] The process of transendothelial migration of melanoma cells has been further investigated by other in vitro studies showing that the ability of these cells to cross the BBB is related to melanotransferrin expression levels on the cell surface, to the fibrinolytic system and to serine proteases released by melanoma cells. [43][44][45] This accumulating evidence indicates that inflammatory stimuli cotribute to the formation of breaches in BBB and of a suitable surrounding in the brain parenchyma for cancer cells.…”
Section: Crossing the Bbbmentioning
confidence: 99%